Genotypic Characteristics of Hepatoblastoma as Detected by Next Generation Sequencing and Their Correlation With Clinical Efficacy - Hu, Huimin; Zhang, Weiling; Zhi, Tian; Li, Jing; Wen, Yuan; Li, Fan; Mei, Yanyan; Huang, Dongsheng (Frontiers in Oncology, 2021)
Background: Hepatoblastoma (HB) is the most common malignant embryonic liver tumor type in children under 3 years of age. In the present study, the next generation sequencing (NGS) method was used to detect the genotype characteristics of HB and summarize the correlation between the common mutation genotypes noted in this disease and the clinical treatment and prognosis. The results may aid clinical prognosis and the successful application of targeted drugs. Methods: Initially, DNA was extracted from tumor tissue specimens and peripheral blood derived from 19 pediatric patients with HB. Subsequently, DNA panel and NGS methods were used to detect tumor diagnosis and the expression levels of treatment-associated genes, followed by the summary of genotype characteristics. In order to further assess the application of immunotherapy in HB, immunohistochemical detection of programmed cell death 1 ligand 1 (PDL1) was performed in combination with tumor mutation burden (TMB) and DNA mismatch repair status analysis. Furthermore, the clinical treatment effect and prognosis of the pediatric patients were statistically analyzed according to the characteristics of the genotype. Overall prognosis and prognostic analyses in different groups were performed by Kaplan-Meier and log-rank tests, respectively. Finally, expression validation and diagnostic analysis of commonly reported genes were performed in the GSE75271 dataset. Results: In the present study, certain mutated genes, including NFE2L2, CTNNB1, MYCN, TP53, AXIN1 and APC were associated with the pathogenesis of HB. During TMB and DNA mismatch repair status analyses, pediatric patients had a low TMB. All of them did not present with microsatellite instability. The immunohistochemical results indicated lower expression levels of PDL1 in HB. The complete remission (CR) rate of pediatric patients in the gene abnormality group was lower than that of the non-reported disease-associated gene abnormality group. The 2-year overall survival rate and disease-free survival rate of 19 pediatric patients with HB were 72.1% and 42.4%, respectively. Conclusion: The genotype changes in HB were more common and the CR rate of the pediatric patients with an altered genotype was lower than that of pediatric patients without an altered genotype. In addition, pediatric patients with HB exhibited lower TMB compared with adult patients.